Respiratory Morbidity and Lung Function Analysis During the First 36 Months of Life in Infants With Bronchopulmonary Dysplasia (BPD) - Chen, Dandan; Chen, Jing; Cui, Ningxun; Cui, Mingling; Chen, Xiaoqian; Zhu, Xueping; Zhu, Xiaoli (Frontiers in Pediatrics, 2020)
Purpose: To explore the lung function of bronchopulmonary dysplasia (BPD) in premature infants to guide clinical prevention, early diagnosis and treatment. Methods: Thirty infants with BPD at 4-36 months of corrected gestational age were enrolled and divided into mild BPD and severe BPD groups. Thirty full-term healthy infants, and 30 non-BPD infants at 4-36 months of corrected gestational age were included as controls. Clinical information, including respiratory infections and re-hospitalization, was compared among these groups. Furthermore, lung function analysis was performed in the infants. Results: The upper respiratory tract infection rate and re-hospitalization rate were significantly higher in the infants with BPD than in the non-BPD infants. The tidal volume/kg, proportion of time to reach peak tidal expiratory flow/total expiratory time, tidal volume exhaled at peak tidal expiratory flow/total tidal volume in BPD group were significantly lower in the BPD group than those in non-BPD group. These values gradually decreased as the severity of BPD increased. The respiratory rate (RR) in BPD group was significantly higher than that in non-BPD group. As the severity of the BPD increased, slope of the descending branch of expiration of tidal breathing flow capacity ring (TBFVL) increased. Conclusion: There is a correlation between the severity of BPD and a poor prognosis of respiratory system. TBFVL can directly reflect the characteristics of Tidal Pulmonary Function in children with different degrees of BPD.